Drivers for OSH interventions in small and medium-sized enterprises. Issue 1 (2nd January 2016) - Cagno, Enrico; Masi, Donato; Leão, Celina Pinto
Abstract : The debate concerning occupational safety and health (OSH) interventions has recently focused on the need of improving the evaluation of interventions, and in particular on the need for providing information about why the intervention worked or not, under what circumstances and in which context. Key concepts in the analysis of the context are the drivers, i.e., those factors enabling, fostering or facilitating OSH interventions. However, the concept of driver for an OSH intervention is both confused and contested. Although the term is widely used, there is little consensus on how drivers should be understood, how important they are in different contexts and how they can facilitate interventions. This exploratory study based on interviews with the owner-managers and the safety officers of small and medium-sized enterprises (SMEs) gives an overview of the most characteristic drivers for OSH interventions. The results will be used to make an initial evaluation of SMEs' needs, and will help orient interventions and future research.